The Impact of Covid-19 in The Economic Sector of Olongapo in Zambales, Philippines - admin-bisnisman, admin-bisnisman; Mobo, Froilan Delute; Rahmat, Abdul; Pagal, Marijoy Samonte (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2020)
Small, local business establishments situated in Olongapo, Zambales, is just one of the many provinces in northern Luzon affected by the COVID-19 crisis. There are also provinces in Zambales that were immensely affected by the COVID-19, and these have an overwhelming impact on large businesses' revenue worldwide, more so in small locally owned business establishments. Business owners are being compelled to take extreme measures to pursue operations. Thus many are apprehensive about their futures. Unemployment has become widespread while the nation's smallest businesses are at risk of bankruptcy. During the nationwide Enhanced Community Quarantine (ECQ) imposed by the Duterte administration, all establishments offering services were temporarily suspended, which led to its temporary rapid closure or, even worse, let go of their employees. For instance, establishments renting inside the Ayala Malls Harborpoint, Hotels in the Barrio Barretto, Olongapo City, and even schools in nearby Zambales were among those affected the smaller the business, the harder the blow. During the Gradual lifting of the quarantine protocols, the situation briefly changed due to the current pandemic. There is a need to rethink strategies on how to uplift the economy, particularly in the localities. An online strategy is one way to help our economy, and it must get the boost needed by implementing online businesses and selling and other online services. These would not just benefit. This will help ensure the blending of the technological platforms that may sustain our local economy. This research will present the dreary effects of COVID-19 in small businesses and study the findings in line with the survey to study and consider solutions to address them.